1965
DOI: 10.1002/ar.1091510107
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic factors in the development of the chick embryo heart

Abstract: Blood flow patterns have been outlined in the chick embryo heart. The initial flow pattern adapts to the heart form but soon vascular forces affect cardiogenesis. Spiralling of the blood streams in the sinus venosus appears to lead to an expansion of this chamber. The atrial septum forms between parallel streams and evidence is presented that blood flow contributes to septation. Interatrial flow develops with a fusion of the inflow streams bringing the entire systemic venous return into the right atrium when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
0

Year Published

1970
1970
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 8 publications
2
32
0
Order By: Relevance
“…Bremer and Jaffee based their conclusions from visual analysis of the forward movements of the blood cells (Bremer, 1932;Jaffee, 1962Jaffee, , 1963Jaffee, , 1965Jaffee, , 1966Jaffee, , 1967. In our experience, it is extremely difficult-in fact, virtually impossible-to delineate the entire course of the two streams by this method.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Bremer and Jaffee based their conclusions from visual analysis of the forward movements of the blood cells (Bremer, 1932;Jaffee, 1962Jaffee, , 1963Jaffee, , 1965Jaffee, , 1966Jaffee, , 1967. In our experience, it is extremely difficult-in fact, virtually impossible-to delineate the entire course of the two streams by this method.…”
Section: Discussionmentioning
confidence: 90%
“…According to the flow-molding theory, there are two spiral streams in the primary heart rube which mold the primitive cardiac chambers and play a major role in the septation process (Spitzer, 1923;Bremer, 1932;Goerttler, 1955;Barthel, 1960;De Vries et al, 1962;Jaffee, 1962Jaffee, , 1963Jaffee, , 1965Jaffee, , 1966Jaffee, , 1967. One stream is the so-called right heart stream which flows selectively through the future right atrium, the right part of the atrioventricular canal, right part of the primitive ventricle, and then spirally through the ventral and left portion of the conotruncus to reach the more caudal branchial arches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Herein we indicate that measurement of blood pressure in the rat embryo is feasible, but with some limitations, and that there may be qualitative hemodynamic differences between the rat and chick embryos. (Pediatr Res 23: 200-205,1988) While searching for the basic mechanism of normal and abnormal morphogenesis of the cardiovascular system, several investigators have been trying to correlate the change of hemodynamics or rheology of the cardiovascular system to morphogenesis (1)(2)(3)(4)(5). These studies have revealed that several teratogenic factors alter the hemodynamics (6-12).…”
mentioning
confidence: 99%